Compare Between Kriging And Fuzzy kriging (Centroid Method) With Application - Jaufar Mousa Mohammed; Dalia Badee Omar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research deals with a comparison of Kriging's method in predicting ordinary and fuzzy data in order to know the best method for future studies. Ordinary data was used in the field of depth of groundwater wells for 37 locations in Kirkuk city, and these data were fuzzy into fuzzy numbers of the trigonometric type that have a function of belonging, Then the centroid of each fuzzy number was found for the purpose of facilitating the calculations. An unknown point was predicted for both the ordinary and fuzzy data. After comparing the results with a standard of least variance, it was found that the fuzzy data had better results than the ordinary data.